Does the Indonesian Capital Market React to Christmas and New Year Holidays? Evidence from LQ45 Companies (2021–2024) - Halida Khairiyah; Tri Joko Prasetyo; Niken Kusumawardani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the stock market reaction to the Christmas and New Year holidays by analyzing abnormal return and trading volume activity for companies consistently listed in the LQ45 Index during 2021–2023. Using a quantitative causal approach and an event study design, the research observes market behavior within a 10 day estimation window and a 10 8day event window surrounding the holiday period. The findings show that abnormal return exhibits limited but notable reactions, with a significant decline observed before the holiday, indicating that investors tend to reduce risk exposure prior to market closure. After the holiday, significant movements still appear, but they remain negative, suggesting that investor activity and confidence have not fully recovered. In contrast, trading volume activity does not show significant differences either before or after the holiday, implying that changes in prices are influenced more by sentiment and price adjustments rather than shifts in trading intensity. These results indicate that the Indonesian capital market demonstrates characteristics of a semi-strong form efficiency, where public information such as national holidays is largely anticipated and absorbed by the market.